2014
DOI: 10.1111/1469-0691.12741
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tularaemia courses: a multicentre study from Turkey

Abstract: In this multicentre study, which is the largest case series ever reported, we aimed to describe the features of tularaemia to provide detailed information. We retrospectively included 1034 patients from 41 medical centres. Before the definite diagnosis of tularaemia, tonsillitis (n = 653, 63%) and/or pharyngitis (n = 146, 14%) were the most frequent preliminary diagnoses. The most frequent clinical presentations were oropharyngeal (n = 832, 85.3%), glandular (n = 136, 13.1%) and oculoglandular (n = 105, 10.1%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 29 publications
3
52
0
1
Order By: Relevance
“…Samples taken from 19 patients (76%) were sent for pathological examination; 13 patients (52%) were reported with cytological findings consistent with abscess content and six (24%) were reported as having granulomatous inflammatory reaction. In the examination of abscess material, 25 patients (100%) Running wound in the neck 3 (12) were reported as ARB negative. All patients were initiated with streptomycin therapy at appropriate doses for 10 days in accordance with the field guideline of the Ministry of Health for tularemia.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Samples taken from 19 patients (76%) were sent for pathological examination; 13 patients (52%) were reported with cytological findings consistent with abscess content and six (24%) were reported as having granulomatous inflammatory reaction. In the examination of abscess material, 25 patients (100%) Running wound in the neck 3 (12) were reported as ARB negative. All patients were initiated with streptomycin therapy at appropriate doses for 10 days in accordance with the field guideline of the Ministry of Health for tularemia.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that almost half of the patients had suppurative inflammation, and only 8% had caseous necrosis. This situation can be interpreted as tuberculosis lymphadenitis in patients having caseification, and it can result in wrong approaches with regard to treatment (12,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erdem et al [24] Tularemia is usually transmitted by direct contact with rodents or drinking and/or well water contaminated by rodents [1,3,9,17] . Our cases were infected probably through a contaminated drinking water source.…”
Section: /205mentioning
confidence: 99%
“…In a multicenter study from Turkey; treatment failure was considered to have occured 48% of patients [24] . The most frequent reasons for failure were the production of suppuration in the lymph nodes after the start of treatment, the formation of new lymphadenomegalies under treatment, and persisting complaints despite two weeks of treatment [24] .…”
Section: /205mentioning
confidence: 99%